2016
DOI: 10.3390/metabo6040047
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics with Nuclear Magnetic Resonance Spectroscopy in a Drosophila melanogaster Model of Surviving Sepsis

Abstract: Abstract:Patients surviving sepsis demonstrate sustained inflammation, which has been associated with long-term complications. One of the main mechanisms behind sustained inflammation is a metabolic switch in parenchymal and immune cells, thus understanding metabolic alterations after sepsis may provide important insights to the pathophysiology of sepsis recovery. In this study, we explored metabolomics in a novel Drosophila melanogaster model of surviving sepsis using Nuclear Magnetic Resonance (NMR), to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…In contrast, it has been a popular organism to understand the genetic determinants of general anesthetic sensitivity, 60,61 and more recently it is being used to understand polytrauma and sepsis. 62,63 The advantages are its easy husbandry, fully understood genetics, large numbers of readily available variants, short generation and life span, and lack of regulatory oversight. While the administration of volatile anesthetics is straightforward, the administration of injectable drugs is not.…”
Section: Drosophila Melanogaster (Fruit Fly)mentioning
confidence: 99%
“…In contrast, it has been a popular organism to understand the genetic determinants of general anesthetic sensitivity, 60,61 and more recently it is being used to understand polytrauma and sepsis. 62,63 The advantages are its easy husbandry, fully understood genetics, large numbers of readily available variants, short generation and life span, and lack of regulatory oversight. While the administration of volatile anesthetics is straightforward, the administration of injectable drugs is not.…”
Section: Drosophila Melanogaster (Fruit Fly)mentioning
confidence: 99%
“…Some studies reported that sepsis survivors exhibited a metabolic signature, characterized by the decreased level of glucose, maltose, tyrosine, beta-alanine, acetate, glutamine, and succinate. [15][16][17] The combined approach of high-throughput techniques contribute to revealing the hidden features of sepsis. The main aim of our study is to preliminarily discuss the capability of the metabolomics approach and explore the molecular mechanism in order to treat SQBS in rats, with an attempt to bring new ideas and fundamental reference material for the future sepsis clinical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, it should be noted that this increase was effectively recovered after MaR1 treatment. Bakalov et al [31] reported that a reduced acetate level may be a metabolic feature in a Drosophila melanogaster model of surviving sepsis. Taken together, the recovery of pyruvate metabolism induced by MaR1 treatment could be contributed to its potential therapeutic effect in CLP-induced septic mice.…”
Section: Discussionmentioning
confidence: 99%